Interlobar division using vessel-sealing system in robot-assisted pulmonary lobectomyCentral MessagePerspective - Masahiro Miyajima, MD; Yuma Shindo, MD; Kodai Tsuruta, MD; Yasuyuki Nakamura, MD; Yoshiaki Takase, MD; Miho Aoyagi, MD; Atsushi Watanabe, MD (JTCVS Techniques)
Objective: We investigated the safety of a novel interlobar fissure division technique using the da Vinci vessel sealing system in robot-assisted pulmonary lobectomy. Methods: The medical records of patients who underwent robotic pulmonary lobectomy with node dissection for primary lung cancer between 2018 and 2020 were reviewed. The inclusion criteria were fulfilled by 111 patients, whose perioperative factors and postoperative results were compared with those previously reported. Furthermore, the new robotic lung interlobar division technique using the da Vinci vessel sealing system without a robotic stapler was evaluated in patients with low-grade incomplete fissure. We considered the Craig and Walker classification of lung fissures grades 1 and 2 as a good adaptation for the vessel sealing system interlobar fissure division. Results: The vessel sealing system group had shorter mean operative and console times (P = .03 and P = .01, respectively) and lesser median intraoperative blood loss (20 mL vs 50 mL; P = .01). The vessel sealing system group had lower surgical complication rates (2.2% vs 20.0%; P = .01). The incidence of persistent postoperative air leak was lower (0% vs 10.0%; P = .06), and fewer robotic stapler cartridges were used during surgery (3.4 vs 5.6; P < .001) in the vessel sealing system group than in the stapler group. Conclusions: We report the safety of using the da Vinci vessel sealing system as an alternative to the use of robotic staples for interlobar fissure division in robot-assisted pulmonary lobectomy. This technique seems easy and feasible though limited to the low-grade incomplete fissure.